Manganese(II) Thiocyanate Complexes with Bis(phosphine Oxide) Ligands: Synthesis and Excitation Wavelength‐Dependent Multicolor Luminescence. Issue 8 (18th February 2020) - Davydova, Maria P.; Bauer, Irina A.; Brel, Valery K.; Rakhmanova, Mariana I.; Bagryanskaya, Irina Yu.; Artem'ev, Alexander V.
Abstract : First examples of luminescent Mn II thiocyanate complexes are presented. A series of such compounds has been synthesized via the reaction of Mn(NCS)2 with bis(phosphine oxides), Ph2 P(O)–X–(O)PPh2, where X = CH2 (L1 ), CH2 CH2 (L2 ), CH2 CH2 CH2 (L3 ), CH2 C(=CH2 )CH2 (L4 ), C(=CH2 )C(=CH2 ) (L5 ) and C≡C (L6 ). The L1, L3 and L4 ligands, when reacted with Mn(NCS)2 on air (EtOH/acetone, r.t.), produce chelate complexes [Mn II (O ^ O)2 (NCS)2 ]. Under similar conditions, L5 gives ionic complex [Mn II (L5 )3 ][Mn II (NCS)4 ], whereas L6 affords chain coordination polymer (CP) [Mn II (L6 )2 (NCS)2 ] n . By contrast, ligand L2 results in formation of mixed‐valent chain CP [Mn II Mn III (L2 )3 (NCS)5 ] n . Complex [Mn(L4 )2 (NCS)2 ] and CP [Mn(L6 )2 (NCS)2 ] n display unique dual luminescence, i.e. the intraligand fluorescence (blue band) and Mn II ‐centered phosphorescence (red band), the ratio of which is largely modulated by excitation wavelength. Through this feature, the luminescence color of these complexes can be smoothly tuned from deep‐blue to red. Complex [Mn(L5 )3 ][Mn(NCS)4 ] shows Mn II ‐based phosphorescence only. Abstract : First representatives of luminescent Mn II thiocyanate complexes were assembled reacting the Mn(NCS)2 with diverse bis(phosphine oxides) ligands of Ph2 P(O)–X–(O)PPh2 type. Some of such complexes feature an intriguing solid‐state dual emission expressed by "blue" and "red" bands which are originated from intraligand fluorescence and Mn 2+ ‐centered phosphorescence, respectively.